Decoration of zinc oxide nanoparticles on vertically aligned single wall carbon nanotubes: An efficient field emitter. (November 2016) - Parveen, Shama; Kumar, Avshish; Husain, Samina; Ali, Javid; Zulfequar, Mohammad; Harsh,; Husain, Mushahid
Graphical abstract: Highlights: ⿢ Vertically Aligned Single wall CNTs have been decorated with ZnO nanoparticles. ⿢ Vertical Alignments of SWCNTs are intact after decoration. ⿢ ZnO coated VA-SWCNTs show remarkable field emission properties. ⿢ Significant increment in current, stability and repeatability were observed. ⿢ The observed FE results were explained in terms of modified surface of VA-SWCNTs. Abstract: In present work, zinc oxide (ZnO) nanoparticles are decorated on the surface of Vertically Aligned-Single Wall Carbon Nanotubes (VA-SWCNTs) to enhance field emission properties of SWCNTs. VA-SWCNTs synthesized by Plasma Enhanced Chemical Vapour Deposition (PECVD) technique are decorated with ZnO nanoparticles by thermal evaporation technique. Modified surface morphologies of as-prepared films were characterized by Atomic Force Microscope (AFM) and Raman spectroscopy to confirm the attachment of ZnO nanoparticles on VA-SWCNTs. Remarkable increase in current density, stability as well as reduction in turn on field were observed in ZnO nanoparticles coated VA-SWCNTs. Attachment of ZnO nanoparticles reduce the turn-on field of VA-SWCNTs field emitters from 2.0 to 1.0 V/μm, while current density increase from 3.6 to 16.8 mA/cm 2 with long term stability and repeatability. The observed results are explained in terms of increased emitting area by modified surface with high field enhancement factor of VA-SWCNTs field emitters.